Use of Fractal Analysis for Complex Assessment of Structural and Functional State of Microhemocirculation in Rats After General Hypothermia - Lutsenko, D. G.; Marchenko, V. S.; Sleta, I. V. (Problems of Cryobiology and Cryomedicine, 2008)
After general cooling of an organism there was recorded the reduction of Hurst exponent for microhemocirculatory bed of fat, muscles, liver and brain cortex (HM) as well as of Hurst exponent of heart rhythm variability (H(R-R)). Under these conditions all the values remain in persistent area. For more distinct estimation of the structural and functional state of microhemociculation there was proposed to apply both Hurst exponents (HM and H(R-R)) simultaneously.